Cloning and characterisation of telomeric DNA from Cladosporium fulvum - Coleman, M.; McHale, M.; Arnau, J.; Watson, A.; Oliver, Richard (1993)
The molecular cloning of DNA from the telomere of one chromosome of Cladosporium fulvum, a fungal pathogen of tomato, is described. The telomeric DNA exhibits tandem repeats of the sequence TTAGGG running 5' to 3' toward the chromosome end. At least 16 tracts of TTAGGG repeats are present in the C. fulvum genome. All such tracts are telomeric, and all chromosome-sized DNAs separated by pulsed-field gel electrophoresis exhibit the repeats. It is probable that tracts of these repeats are present at all chromosome termini. The cloned telomeric DNA exhibits 19 copies of the TTAGGG hexanucleotide motif, and evidence is presented indicating that all tracts of TTAGGG repeats are quite short. Telomere-linked restriction-fragment length polymorphisms between races of C. fulvum have been detected, and groupings based on these polymorphisms are consistent with those determined previously. Sub-telomeric DNA, centromere proximal to the cloned telomeric DNA, contains sequences reiterated many times in the genome; some of these repeats are at non-terminal locations. Partial sequence analysis indicates an absence of homology with the sub-telomeric DNA of other organisms.